Learners' Knowledge Gaps as an Obstacle to Implementing Innovative Pedagogy in Accounting - Ngwenya, Jabulisile; Arek-Bawa, Orhe; Ndovela, Sithembele (CV Sinergi Ilmu dan Publikasi, 2026)
This study examines how learners’ knowledge gaps hinder the effective implementation of innovative pedagogical practices in accounting classrooms. Framed within an interpretive paradigm, the research employed a qualitative case study approach involving eight accounting teachers who were purposively selected. Data collected through focus group discussions revealed that many learners enter the Further Education and Training (FET) phase without foundational knowledge in financial literacy, numeracy, and key accounting concepts. This lack of preparedness disrupts lesson planning, delays curriculum progression, and limits the implementation of innovative teaching strategies. Although teachers often resort to remedial instruction, the tension between the need for remedial support and the inflexible demands of strict curriculum pacing illustrates a systemic misalignment with constructivist principles. The study suggests the need for early intervention in lower grades and increased curricular flexibility. It offers valuable insights for the Department of Basic Education and school stakeholders to create opportunities for targeted learner support, including structured Grade 10 catch-up programs and differentiated instructional approaches without disrupting curriculum flow or compromising teaching quality.